2011
DOI: 10.1152/jn.00907.2010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial summation in macaque parietal area 7a follows a winner-take-all rule

Abstract: While neurons in posterior parietal cortex have been found to signal the presence of a salient stimulus among multiple items in a display, spatial summation within their receptive field in the absence of an attentional bias has never been investigated. This information, however, is indispensable when one investigates the mechanisms of spatial attention and competition between multiple visual objects. To examine the spatial summation rule in parietal area 7a neurons, we trained rhesus monkeys to fixate on a cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In previous research, most of the singleunit studies have focused on extrastriate areas because the receptive fields of V1 neurons are too small to cover multiple objects. They showed that in V2 (Luck et al 1997), V4 (Gawne and Martin 2002), V7a (Oleksiak et al 2011), IT (Zoccolan et al 2005), and MT (Recanzone et al 1997), neuronal responses to multiple stimuli can be predicted by either the weighted average or the maximum of the responses of the constituent stimuli. Some researchers have proposed even more complicated algorithms, such as divisive inhibition (Britten and Heuer 1999;Simoncelli and Heeger 1998).…”
Section: Implications For Spatial Summation In V1mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, most of the singleunit studies have focused on extrastriate areas because the receptive fields of V1 neurons are too small to cover multiple objects. They showed that in V2 (Luck et al 1997), V4 (Gawne and Martin 2002), V7a (Oleksiak et al 2011), IT (Zoccolan et al 2005), and MT (Recanzone et al 1997), neuronal responses to multiple stimuli can be predicted by either the weighted average or the maximum of the responses of the constituent stimuli. Some researchers have proposed even more complicated algorithms, such as divisive inhibition (Britten and Heuer 1999;Simoncelli and Heeger 1998).…”
Section: Implications For Spatial Summation In V1mentioning
confidence: 99%
“…However, there has been little evidence for this summation, even in the earliest visual cortical area V1. Single-unit recording studies have focused on extrastriate areas (Gawne and Martin 2002;Luck et al 1997;Oleksiak et al 2011;Recanzone et al 1997;Zoccolan et al 2005) and showed that in these areas neuronal responses to a multiobject stimulus could be predicted by either the weighted average or the maximum response to its constituent components. However, because the receptive fields of neurons in V1 are too small to cover multiple objects, very few electrophysiological studies have tried to tackle how V1 responds to multiple objects at the single unit level.…”
mentioning
confidence: 99%
“…A number of networks in visual and parietal cortex exploit winner-take-all (WTA) coding schemes. 23, 28 In WTA coding, input neurons compete for output neuron activation, with the response of the output cell most closely resembling the firing rate and tuning characteristics of the strongest input. Physiologically, WTA rules are thought to be involved in visual attention and saliency detection throughout the visual system, including object orientation and direction.…”
Section: Methodsmentioning
confidence: 99%
“…23, 28, 40 Specifically, winner-take-all particle swarm optimization (WTAPSO) is a dynamic, hierarchical topology that utilizes winner-take-all coding strategies found in the visual system which shows improved performance on high-dimensional problems as compared to traditional particle swarm networks (Fig 2.). We begin with a derivation of WTAPSO.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that the general tendency is for the response to two stimuli to be near the weighted average of the responses to each stimulus presented separately (Moran and Desimone, 1985; Luck et al, 1997; Reynolds et al, 1999; Reynolds and Desimone, 2003; Zoccolan et al, 2005). Other studies have found that it was more common for the response to two stimuli to be similar in magnitude to the larger of the responses to the two stimuli presented separately, a winner-take-all or “MAX” result, at least for high-contrast stimuli (Sato, 1989; Heuer and Britten, 2002; Rolls et al, 2003; Lampl et al, 2004; Finn and Ferster, 2007; Oleksiak et al, 2011). In an attempt to limit the possible interactions at earlier processing stages, studies in this laboratory used two stimuli that were presented as far apart from each other as possible while still remaining within the RF (Gawne and Martin, 2002a; Gawne, 2008), and found a strong tendency for a MAX operation.…”
Section: Introductionmentioning
confidence: 98%